Stimulating students to speak up through presentation in business English class - Lia Agustina (English, 2019)
Doing a presentation is not easy; it needs self-confidence, practice, and knowledge. Assigning students to have presentations would be a great practice for both in and outside the classroom; it is a skill of most people will need in the working field. Doing presentations in the English Foreign Language classroom would practice all language systems areas (vocabulary, grammar, discourse, and phonology) and skills (speaking, reading, writing and listening), it would build students’ confidence, fluency, and knowledge of English. The teacher-researcher used the Action Research Method proposed by Kemmis and Taggart (1989) to illustrate the process of planning, action, observation, and reflection that formed spiral moments. The purpose of the study was used to see the improvement of the students’ self-confidence and the ability to speak up when performing a business meeting project. The subject was 32 students of the Accounting Department who were studying at the fourth semester in the year of 2016/2017. The result of the study showed that most students showed an improvement in all four language skills but the speaking skill had the greatest improvement. Most students seemed developed their motivation and participated in learning activities with interest and enjoyment.